Time to Endovascular Treatment and Outcome in Acute Ischemic Stroke: MR CLEAN Registry Results. Issue 3 (17th July 2018) - Mulder, Maxim J.H.L.; Jansen, Ivo G.H.; Goldhoorn, Robert-Jan B.; Venema, Esmee; Chalos, Vicky; Compagne, Kars C.J.; Roozenbeek, Bob; Lingsma, Hester F.; Schonewille, Wouter J.; van den Wijngaard, Ido R.; Boiten, Jelis; Albert Vos, Jan; et al.
Abstract : Background: Randomized, clinical trials in selected acute ischemic stroke patients reported that for every hour delay of endovascular treatment (EVT), chances of functional independence diminish by up to 3.4%. These findings may not be fully generalizable to clinical practice because of strict in- and exclusion criteria in these trials. Therefore, we aim to assess the association of time to EVT with functional outcome in current, everyday clinical practice. Methods: The MR CLEAN Registry (Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in The Netherlands) is an ongoing, prospective, observational study in all centers that perform EVT in The Netherlands. Data were analyzed from patients treated between March 2014 and June 2016. In the primary analysis we assessed the association of time from stroke onset to start of EVT and time from stroke onset to successful reperfusion with functional outcome (measured with the modified Rankin Scale), by means of ordinal logistic regression. Results: We analyzed 1488 patients with acute ischemic stroke who underwent EVT. An increased time to start of EVT was associated with worse functional outcome (adjusted common odds ratio, 0.83 per hour; 95% confidence interval, 0.77–0.89) and a 2.2% increase in mortality. Every hour increase from stroke onset to EVT start resulted in a 5.3% decreased probability of functional independence (modified Rankin Scale, 0–2). In the 742 patients with successful reperfusion, every hour increase from stroke onset to reperfusion was associated with a 7.7% decreased probability of functional independence. Conclusions: Time to EVT for acute ischemic stroke in current clinical practice is strongly associated with functional outcome. Our data suggest that this association might be even stronger than previously suggested in reports on more selected patient populations from randomized, controlled trials. These findings emphasize that functional outcome of EVT patients can be greatly improved by shortening onset to treatment times. Abstract : Supplemental Digital Content is available in the text.